CoMo catalyst suitable for phenol hydrodeoxygenation reaction as well as preparation method and application of CoMo catalyst
By preparing the Co-MoOx/CN catalyst, the problem of low hydrodeoxygenation reaction efficiency in the prior art was solved, and the efficient catalytic conversion of phenol to cyclohexane under mild conditions was achieved, and the catalyst had good cycle stability and easy recovery.
Patent Information
- Application Number
- CN202510292525.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-06-13
AI Technical Summary
The existing phenol hydrodeoxygenation catalyst has low reaction efficiency under mild conditions, and the reaction conditions are harsh and the reaction time is long.
By using the preparation method of CoMo catalyst, the Co-MoOx/CN catalyst is obtained by dissolving molybdate and cobalt salts in a specific solvent, adding organic ligands, mixed stirring, centrifugal washing and two-step pyrolysis treatment.
The catalyst significantly improves the conversion rate of phenol hydrodeoxygenation and the yield of cyclohexane under mild conditions, and has excellent cycle stability and is easy to recover.
Smart Images

Figure CN120132866A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the preparation of a MOFs-derived material, and particularly to a preparation method of a CoMo catalyst suitable for the hydrodeoxygenation reaction of phenol. Background Art
[0002] Metal-organic frameworks (MOFs) are porous materials with a periodic network structure formed by the self-assembly of metal ions or metal clusters and organic ligands through coordination bonds. They have the advantages of large specific surface area, regular pore channels, and adjustable structures and properties, and are widely used as self-synthesis precursors and templates for various porous materials. By pyrolysis treatment in an inert atmosphere, metal nanoparticles reduced by carbon can be obtained embedded in a porous carbon support, and compared with traditional supported catalysts, the catalytic activity and stability are significantly improved.
[0003] Currently, common hydrodeoxygenation catalysts for phenolic substances include metal sulfides, phosphides, carbides, nitrides, and supported metal catalysts. Metal sulfides such as MoS 2 , CoMoS 2 etc., have good hydrodeoxygenation performance but are prone to deactivation. For metal phosphides, carbides, nitrides, Ni 2 P / SiO 2 and Mo 2C shows good hydrodeoxygenation potential, but like sulfides, its stability and renewability also need to be improved. Among supported metal catalysts, noble metals such as Pt, Pd, Ru and transition metals such as Ni, Co have excellent hydrogenation performance. Yang et al. prepared well-dispersed ultrasmall Ru clusters encapsulated in high-aluminum ZSM-5 zeolite by an in-situ two-stage hydrothermal synthesis method. At 150 °C and 5 MPa, the cyclohexane yield reached 90% (Yang, J.; He, Y.; He, J.; Liu, Y.; Geng, H.; Chen, S.; Lin, L.; Liu, M.; Chen, T.; Jiang, Q.; Weckhuysen, B. M.; Luo, W.; Wu, Z. Enhanced Catalytic Performance through In Situ Encapsulation of Ultrafine Ru Clusters within a High-Aluminum Zeolite. ACS Catal. 2022, 12(3), 1847–1856.). Robinson et al. reported that PtMo can catalyze the deoxygenation of m-cresol through a pathway involving an initial tautomerization step, and the deoxygenation is significant even in the absence of an acidic support material (Robinson, A.; Ferguson, G. A.; Gallagher, J. R.; Cheah, S.; Beckham, G. T.; Schaidle, J. A.; Hensley, J. E.; Medlin, J. W. Enhanced Hydrodeoxygenation of m-Cresol over Bimetallic Pt–Mo Catalysts through an Oxophilic Metal-Induced Tautomerization Pathway. ACS Catal. 2016, 6(7), 4356–4368.). Although supported noble metal catalysts can achieve efficient conversion under mild conditions, they are expensive and scarce in reserves. In contrast, non-noble metal catalysts have received extensive attention due to their low price.Han et al. prepared bimetallic Ni-Fe nanoparticles supported on mesoporous carbon spheres (MCS). By forming the Ni-Fe alloy phase, the catalytic performance of the Ni-Fe catalyst for the hydrodeoxygenation (HDO) of phenol is superior to that of monometallic Ni and Fe catalysts. At 5 MPa and 250 °C, the yield of cyclohexane is 93.8% (Han, Q.; Rehman, M. U.; Wang, J.; Rykov, A.; Gutiérrez, O. Y.; Zhao, Y.; Wang, S.; Ma, X.; Lercher, J. A. The Synergistic Effect between Ni Sites and Ni-Fe Alloy Sites on Hydrodeoxygenation of Lignin-Derived Phenols. Appl. Catal. B Environ. 2019, 253, 348–358.). Liu et al. used CoNx@NC to catalyze the hydrogenation of eugenol. After adding the solid acid HZSM-5, the yield of propylcyclohexane reached 99.1% (Liu, X.; Xu, L.; Xu, G.; Jia, W.; Ma, Y.; Zhang, Y. Selective Hydrodeoxygenation of Lignin-Derived Phenols to Cyclohexanols or Cyclohexanes over Magnetic CoNx@NC Catalysts under Mild Conditions. ACS Catal. 2016, 6(11), 7611–7620.). Although these non-noble metal catalysts show high hydrogenation activity, the reaction conditions are still harsh and the reaction time is long.
[0004] Therefore, aiming at the existing problems of the above-mentioned phenol hydrodeoxygenation catalysts, based on a series of advantages of MOF materials, it is still necessary to develop a new type of efficient MOF-derived non-noble metal catalyst to convert lignin-derived phenolic compounds under mild conditions. Summary of the Invention
[0005] The object of the present invention is to provide a preparation method of a CoMo catalyst suitable for the phenol hydrodeoxygenation reaction, which is used to efficiently catalyze the hydrodeoxygenation of phenol to cyclohexane under mild conditions.
[0006] The object of the present invention can be achieved by the following technical solutions:
[0007] A preparation method of a CoMo catalyst suitable for the phenol hydrodeoxygenation reaction, the specific steps are as follows:
[0008] (1) Dissolve molybdic acid and cobalt salt in deionized water and methanol respectively to obtain metal salt solutions; dissolve the organic ligand in methanol to obtain an organic ligand solution.
[0009] (2) Pour the metal cobalt salt solution into the metal molybdenum heteropolyacid solution at room temperature, mix and stir, then add the organic ligand solution, continue to stir, centrifuge, wash and dry to obtain the precursor CoMo bimetallic MOFs.
[0010] (3) Carry out two-step pyrolysis of the precursor CoMo bimetallic MOFs prepared in step (2) in a tubular furnace,
[0011] to obtain the CoMo catalyst Co-MoOx / CN.
[0012] Further, in step (1), the molybdic acid is phosphomolybdic acid hydrate, the cobalt salt is cobalt nitrate hexahydrate, and the organic ligand is 2-methylimidazole.
[0013] Further, in step (1), the concentration of the metal cobalt salt solution is 0.05 - 0.1 mol / L, the concentration of the metal molybdenum heteropolyacid solution is 0 - 0.005 mol / L, and the concentration of the organic ligand solution is 0.5 - 1 mol / L.
[0014] Further, in step (1), the addition ratio of the metal cobalt salt solution, the metal molybdenum heteropolyacid solution and the organic ligand solution is 1:1:1 - 5:1:5.
[0015] Further, in step (2), the mixing and stirring time is 0.2 - 0.8 h.
[0016] Further, in step (2), the continuous stirring time after adding the 2-methylimidazole solution is 1 - 5 h.
[0017] Further, in step (3), the two-step pyrolysis is carried out under argon and air respectively.
[0018] Further, in step (3), the pyrolysis temperature under argon atmosphere is 700 - 900 °C, and the pyrolysis time is 1 - 4 h.
[0019] Further, in step (3), the pyrolysis temperature under air atmosphere is 150 - 250 °C, and the pyrolysis time is 1 - 3 h.
[0020] The present invention provides a CoMo catalyst suitable for the hydrodeoxygenation reaction of phenol. Further, the specific reaction steps are as follows: phenol, n-octane, and CoMo catalyst Co-MoOx / CN are successively added into a high-pressure reaction kettle, hydrogen is filled, and the mixture is heated to 200-240 °C under stirring and kept at a constant temperature for 0.5-4 h. After the reaction is completed, the reaction kettle is cooled to room temperature, and the CoMo catalyst Co-MoOx / CN is separated from the reaction solution by filtration to obtain cyclohexane.
[0021] Further, the mass ratio of the raw material phenol to the CoMo catalyst Co-MoOx / CN is 0.1-0.9.
[0022] Compared with the prior art, the technical effects of the present invention are as follows:
[0023] (1) The CoMo catalyst Co-MoOx / CN involved in the present invention has a hierarchical porous structure of micropores, mesopores, and macropores, which shortens the mass transfer distance and increases the substrate accessibility.
[0024] (2) In the CoMo catalyst Co-MoOx / CN involved in the present invention, the presence of N and graphitic carbon can enhance electron transfer and promote the transfer of electrons from Co to Mo, thereby making the adsorption ability of Mo for hydroxyl species stronger.
[0025] (3) The active sites of the CoMo catalyst Co-MoOx / CN involved in the present invention are fully exposed after air calcination, and there are active sites Co and Mo in both the reduced state and the oxidized state, which can effectively activate hydrogen and adsorb hydroxyl species. Under a hydrogen pressure of 0.5 MPa, it can catalyze phenol to reach 100%
[0026] conversion rate and 88.3% cyclohexane yield.
[0027] (4) The CoMo catalyst Co-MoOx / CN involved in the present invention has excellent cyclic stability, is easy to separate and recover after the reaction, and can be recycled many times and maintain good reaction activity after washing and drying. Description of the Drawings
[0028] Figure 1 XRD patterns of CoOx / CN and Co-MoOx / CN obtained in Examples 1-6;
[0029] Figure 2a SEM image of the CoOx / CN precursor obtained in Example 1; Figure 2b SEM image of the CoOx / CN obtained in Example 1;
[0030] Figure 3a SEM image of the a-Co-MoOx / CN precursor obtained in Example 2; Figure 3bSEM image of a-Co-MoOx / CN obtained in Example 2;
[0031] Figure 4a SEM image of the precursor of b-Co-MoOx / CN obtained in Example 3; Figure 4b SEM image of b-Co-MoOx / CN obtained in Example 3;
[0032] Figure 5a SEM image of the precursor of c-Co-MoOx / CN obtained in Example 4; Figure 5b SEM image of c-Co-MoOx / CN obtained in Example 4; Figure 5c TEM image of c-Co-MoOx / CN obtained in Example 4;
[0033] Figure 6a SEM image of the precursor of d-Co-MoOx / CN obtained in Example 5; Figure 6b SEM image of d-Co-MoOx / CN obtained in Example 5;
[0034] Figure 7a SEM image of the precursor of e-Co-MoOx / CN obtained in Example 6; Figure 7b SEM image of e-Co-MoOx / CN obtained in Example 6;
[0035] Figure 8a SEM image of f-Co-MoOx / CN obtained in Example 7;
[0036] Figure 8b SEM image of g-Co-MoOx / CN obtained in Example 8;
[0037] Figure 8c SEM image of h-Co-MoOx / CN obtained in Example 9;
[0038] Figure 8d SEM image of i-Co-MoOx / CN obtained in Example 10;
[0039] Figure 9 BET diagram of c-Co-MoOx / CN obtained in Example 4;
[0040] Figure 10 Performance test result diagram of CoMo catalysts (CoOx / CN, a-Co-MoOx / CN, b-Co-MoOx / CN, c-Co-MoOx / CN, d-Co-MoOx / CN, e-Co-MoOx / CN) with different phosphomolybdic acid addition contents for the hydrogenation and deoxygenation of phenol to cyclohexane in Example 11;
[0041] Figure 11 Performance test results of CoMo catalysts (c-Co-MoOx / CN, h-Co-MoOx / CN, i-Co-MoOx / CN) with different air calcination temperatures in Example 12 for the hydrogenation and deoxygenation of phenol to cyclohexane;
[0042] Figure 12 Performance test results of c-Co-MoOx / CN obtained in Example 13;
[0043] Figure 13 Results of the effect of reaction pressure on the hydrogenation and deoxygenation of phenol to cyclohexane in Example 14. Detailed implementation mode
[0044] The present invention will be further described below through examples in conjunction with the accompanying drawings, but the implementation and protection scope of the present invention are not limited thereto.
[0045] Example 1
[0046] This example provides a preparation method of a single-metal Co catalyst CoOx / CN without adding phosphomolybdic acid. The specific steps are as follows:
[0047] Dissolve cobalt nitrate hexahydrate (0.722 g, 2.48 mmol) and 2-methylimidazole (1.629 g, 19.84 mmol) in 25 ml of methanol respectively. After ultrasonic treatment, quickly pour the 2-methylimidazole solution into the cobalt nitrate solution under stirring, stir for 3 h, centrifuge and wash. The obtained purple precipitate is dried overnight in an oven at 60 °C to obtain the precursor ZIF-67 of the single-metal Co catalyst CoOx / CN. Place the precursor ZIF-67 in a tubular furnace, and heat it to 900 °C at a heating rate of 5 °C / min under an argon atmosphere, and keep it at a constant temperature for 2 h. When it is cooled to 250 °C, replace argon with air and continue to keep it at a constant temperature for 1.5 h to obtain the single-metal Co catalyst CoOx / CN.
[0048] Figure 1 XRD pattern of the single-metal Co catalyst CoOx / CN obtained in this example. The three diffraction peaks at 44.2°, 51.5°, and 75.8° in the figure correspond to the characteristic peaks of elemental Co, and the diffraction peaks at 19°, 31.3°, 36.8°, 38.5°, 44.8°, 55.6°, 59.4°, and 65.2° correspond to Co 3 O 4 , and the diffraction peak at 26.3° corresponds to graphite carbon.
[0049] Figure 2a SEM image of the CoOx / CN precursor ZIF-67 obtained in this example, Figure 2bIt is the SEM image of the single-metal Co catalyst CoOx / CN obtained in this example. It can be seen that ZIF-67 has a rhombic dodecahedron structure. After pyrolysis, CoOx / CN presents an irregular morphology with a rough surface.
[0050] Example 2
[0051] This example provides a preparation method of a CoMo catalyst a-Co-MoOx / CN. The specific steps are as follows:
[0052] Dissolve cobalt nitrate hexahydrate (0.722 g, 2.48 mmol) and 2-methylimidazole (1.629 g, 19.84 mmol) in 25 ml of methanol respectively. After ultrasonic treatment, quickly pour the cobalt nitrate solution into an aqueous solution (10 ml) containing 15 mg of phosphomolybdic acid hydrate under stirring, and stir for 30 min. After 30 min, add the 2-methylimidazole solution and continue to stir for 3 h. Centrifuge and wash. The obtained blue-violet precipitate is dried overnight in an oven at 60 °C to obtain the precursor of the CoMo catalyst a-Co-MoOx / CN. Place the precursor in a tubular furnace and heat it to 900 °C at a heating rate of 5 °C / min under an argon atmosphere, and keep it at a constant temperature for 2 h. When it is cooled to 250 °C, replace argon with air and continue to keep it at a constant temperature for 1.5 h to obtain the CoMo catalyst a-Co-MoOx / CN.
[0053] Figure 1 It is the XRD pattern of the CoMo catalyst a-Co-MoOx / CN obtained in this example. The three diffraction peaks at 44.2°, 51.5°, and 75.8° in the figure correspond to the characteristic peaks of elemental Co, and the diffraction peak at 36.8° corresponds to Co 3 O 4 , and the diffraction peak at 26.3° corresponds to graphite carbon.
[0054] Figure 3a It is the SEM image of the a-Co-MoOx / CN precursor obtained in this example, Figure 3b It is the SEM image of a-Co-MoOx / CN obtained in this example. It can be seen that the precursor has a rhombic dodecahedron structure, and phosphomolybdic acid etches holes in the dodecahedron. After pyrolysis, a-Co-MoOx / CN presents an irregular morphology with a rough surface.
[0055] Example 3
[0056] This example provides a preparation method of a CoMo catalyst b-Co-MoOx / CN. The specific steps are as follows:
[0057] Cobalt nitrate hexahydrate (0.722 g, 2.48 mmol) and 2-methylimidazole (1.629 g, 19.84 mmol) were separately dissolved in 25 ml of methanol. After ultrasonic treatment, the cobalt nitrate solution was rapidly poured into an aqueous solution (10 ml) containing 30 mg of phosphomolybdic acid hydrate under stirring, and stirred for 30 min. After 30 min, the 2-methylimidazole solution was added, and stirring was continued for 3 h. After centrifugation and washing, the obtained blue-violet precipitate was dried overnight in an oven at 60 °C to obtain a precursor of the CoMo catalyst b-Co-MoOx / CN. The precursor was placed in a tubular furnace and heated to 900 °C at a heating rate of 5 °C / min under an argon atmosphere, and kept at a constant temperature for 2 h. When cooled to 250 °C, the argon was replaced with air and kept at a constant temperature for another 1.5 h to obtain the CoMo catalyst b-Co-MoOx / CN.
[0058] Figure 1 is the XRD pattern of the CoMo catalyst b-Co-MoOx / CN obtained in this example. The three diffraction peaks at 44.2°, 51.5°, and 75.8° in the figure correspond to the characteristic peaks of elemental Co, and the diffraction peak at 36.8° corresponds to Co 3 O 4 , and the diffraction peaks at 39.9°, 42.3°, and 46.3° correspond to Co 3 Mo 3 N, and the diffraction peak at 26.3° corresponds to graphite carbon.
[0059] Figure 4a is the SEM image of the b-Co-MoOx / CN precursor obtained in this example, Figure 4b is the SEM image of the b-Co-MoOx / CN obtained in this example. It can be seen that the precursor has a rhombic dodecahedron structure, and phosphomolybdic acid etches holes on the dodecahedron. After pyrolysis, b-Co-MoOx / CN presents an irregular morphology with a rough surface.
[0060] Example 4
[0061] This example provides a preparation method of a CoMo catalyst c-Co-MoOx / CN, and the specific steps are as follows:
[0062] Cobalt nitrate hexahydrate (0.722 g, 2.48 mmol) and 2-methylimidazole (1.629 g, 19.84 mmol) were separately dissolved in 25 ml of methanol. After ultrasonic treatment, the cobalt nitrate solution was quickly poured into an aqueous solution (10 ml) containing 45 mg of phosphomolybdic acid hydrate under stirring, and stirred for 30 min. After 30 min, the 2-methylimidazole solution was added, and stirring was continued for 3 h. After centrifugation and washing, the obtained blue-violet precipitate was dried overnight in an oven at 60 °C to obtain the precursor of the CoMo catalyst c-Co-MoOx / CN. The precursor was placed in a tubular furnace and heated to 900 °C at a heating rate of 5 °C / min under an argon atmosphere and held at a constant temperature for 2 h. When cooled to 250 °C, the argon was replaced with air and held at a constant temperature for another 1.5 h to obtain the CoMo catalyst c-Co-MoOx / CN.
[0063] Figure 1 is the XRD pattern of the CoMo catalyst c-Co-MoOx / CN obtained in this example. The three diffraction peaks at 44.2°, 51.5°, and 75.8° in the figure correspond to the characteristic peaks of elemental Co, and the diffraction peaks at 36.8° and 65.2° correspond to Co 3 O 4 , and the diffraction peaks at 39.9°, 42.3°, and 46.3° correspond to Co 3 Mo 3 N, the diffraction peak at 26.5° corresponds to CoMoO 4 , and the diffraction peak at 26.3° corresponds to graphite carbon.
[0064] Figure 5a is the SEM image of the c-Co-MoOx / CN precursor obtained in this example, Figure 5b is the SEM image of c-Co-MoOx / CN obtained in this example. It can be seen that the precursor has a rhombic dodecahedron structure, and phosphomolybdic acid etches holes in the dodecahedron. After pyrolysis, c-Co-MoOx / CN presents an irregular morphology with a rough surface. Figure 5c is the TEM image of c-Co-MoOx / CN obtained in this example. It can be seen that the carbon film of this material is in an amorphous state, and metal particles are evenly distributed on the carbon support.
[0065] Figure 9 is the BET diagram of the CoMo catalyst c-Co-MoOx / CN obtained in this example. It can be seen that the adsorption-desorption curve shows a type IV isotherm with an obvious hysteresis loop, indicating the presence of mesopores; there is an obvious upward trend in the curve at P / P 0 = 0.95 - 1, indicating the presence of macropores; it can also be concluded from the pore size distribution curve that Co-MoOx / CN has a porous structure with micropores, mesopores, and macropores.
[0066] Example 5
[0067] This example provides a method for preparing a CoMo catalyst d-Co-MoOx / CN, and the specific steps are as follows:
[0068] Dissolve cobalt nitrate hexahydrate (0.722 g, 2.48 mmol) and 2-methylimidazole (1.629 g, 19.84 mmol) separately in 25 ml of methanol. After ultrasonic treatment, quickly pour the cobalt nitrate solution into an aqueous solution (10 ml) containing 60 mg of phosphomolybdic acid hydrate under stirring, and stir for 30 min. After 30 min, add the 2-methylimidazole solution, continue to stir for 3 h, centrifuge and wash. The obtained blue-violet precipitate is dried overnight in an oven at 60 °C to obtain a precursor of the CoMo catalyst d-Co-MoOx / CN. Place the precursor in a tubular furnace, and heat it to 900 °C at a heating rate of 5 °C / min under an argon atmosphere, and keep it at a constant temperature for 2 h. When it is cooled to 250 °C, replace the argon with air and continue to keep it at a constant temperature for 1.5 h to obtain the CoMo catalyst d-Co-MoOx / CN.
[0069] Figure 1 is the XRD pattern of the CoMo catalyst d-Co-MoOx / CN obtained in this example. The three diffraction peaks at 44.2°, 51.5°, and 75.8° in the figure correspond to the characteristic peaks of elemental Co, and the diffraction peaks at 36.8° and 65.2° correspond to Co 3 O 4 , and the diffraction peaks at 39.9°, 42.3°, 46.3°, and 72.8° correspond to Co 3 Mo 3 N, the diffraction peak at 26.5° corresponds to CoMoO 4 , and the diffraction peak at 26.3° corresponds to graphite carbon.
[0070] Figure 6a is the SEM image of the d-Co-MoOx / CN precursor obtained in this example, Figure 6b is the SEM image of the d-Co-MoOx / CN obtained in this example. It can be seen that the precursor has a rhombic dodecahedron structure, and phosphomolybdic acid etches holes in the dodecahedron. After pyrolysis, d-Co-MoOx / CN presents an irregular morphology with a rough surface.
[0071] Example 6
[0072] This example provides a method for preparing a CoMo catalyst e-Co-MoOx / CN, and the specific steps are as follows:
[0073] Cobalt nitrate hexahydrate (0.722 g, 2.48 mmol) and 2-methylimidazole (1.629 g, 19.84 mmol) were separately dissolved in 25 ml of methanol. After ultrasonic treatment, the cobalt nitrate solution was quickly poured into an aqueous solution (10 ml) containing 75 mg of phosphomolybdic acid hydrate under stirring, and stirred for 30 min. After 30 min, the 2-methylimidazole solution was added, and stirring was continued for 3 h. After centrifugation and washing, the obtained blue-violet precipitate was dried overnight in an oven at 60 °C to obtain the precursor of the CoMo catalyst e-Co-MoOx / CN. The precursor was placed in a tubular furnace and heated to 900 °C at a heating rate of 5 °C / min under an argon atmosphere and kept at a constant temperature for 2 h. When cooled to 250 °C, the argon was replaced with air and kept at a constant temperature for another 1.5 h to obtain the CoMo catalyst e-Co-MoOx / CN.
[0074] Figure 1 is the XRD pattern of the CoMo catalyst e-Co-MoOx / CN obtained in this example. The three diffraction peaks at 44.2°, 51.5°, and 75.8° in the figure correspond to the characteristic peaks of elemental Co, and the diffraction peaks at 36.8° and 65.2° correspond to Co 3 O 4 , and the diffraction peaks at 32.5°, 35.5°, 39.9°, 42.3°, 46.3°, and 72.8° correspond to Co 3 Mo 3 N, and the diffraction peak at 26.5° corresponds to CoMoO 4 , and the diffraction peak at 26.3° corresponds to graphite carbon.
[0075] Figure 7a is the SEM image of the e-Co-MoOx / CN precursor obtained in this example, Figure 7b is the SEM image of the e-Co-MoOx / CN obtained in this example. It can be seen that the precursor has a rhombic dodecahedron structure, and phosphomolybdic acid etches holes in the dodecahedron. After pyrolysis, e-Co-MoOx / CN presents an irregular morphology with a rough surface.
[0076] Example 7
[0077] This example provides a preparation method of a CoMo catalyst f-Co-MoOx / CN, and the specific steps are as follows:
[0078] Cobalt nitrate hexahydrate (0.722 g, 2.48 mmol) and 2-methylimidazole (1.629 g, 19.84 mmol) were separately dissolved in 25 ml of methanol. After ultrasonic treatment, the cobalt nitrate solution was quickly poured into an aqueous solution (10 ml) containing 45 mg of phosphomolybdic acid hydrate under stirring, and stirred for 30 min. After 30 min, the 2-methylimidazole solution was added, and stirring was continued for 3 h. After centrifugation and washing, the obtained blue-violet precipitate was dried overnight in an oven at 60 °C to obtain the precursor of the CoMo catalyst f-Co-MoOx / CN. The precursor was placed in a tubular furnace and heated to 800 °C at a heating rate of 5 °C / min under an argon atmosphere and kept at a constant temperature for 2 h. When cooled to 250 °C, the argon was replaced with air and kept at a constant temperature for another 1.5 h to obtain the CoMo catalyst f-Co-MoOx / CN.
[0079] Figure 8a Figure is the SEM image of f-Co-MoOx / CN obtained in this example. It can be seen that f-Co-MoOx / CN was not completely calcined and showed an irregular morphology with a rough surface after calcination.
[0080] Example 8
[0081] This example provides a method for preparing a CoMo catalyst g-Co-MoOx / CN, and the specific steps are as follows:
[0082] Cobalt nitrate hexahydrate (0.722 g, 2.48 mmol) and 2-methylimidazole (1.629 g, 19.84 mmol) were separately dissolved in 25 ml of methanol. After ultrasonic treatment, the cobalt nitrate solution was quickly poured into an aqueous solution (10 ml) containing 45 mg of phosphomolybdic acid hydrate under stirring, and stirred for 30 min. After 30 min, the 2-methylimidazole solution was added, and stirring was continued for 3 h. After centrifugation and washing, the obtained blue-violet precipitate was dried overnight in an oven at 60 °C to obtain the precursor of the CoMo catalyst g-Co-MoOx / CN. The precursor was placed in a tubular furnace and heated to 700 °C at a heating rate of 5 °C / min under an argon atmosphere and kept at a constant temperature for 2 h. When cooled to 250 °C, the argon was replaced with air and kept at a constant temperature for another 1.5 h to obtain the CoMo catalyst g-Co-MoOx / CN.
[0083] Figure 8b Figure Figure 8b is the SEM image of g-Co-MoOx / CN obtained in this example. It can be seen that g-Co-MoOx / CN was not completely calcined and showed an irregular morphology with a rough surface after calcination.
[0084] Example 9
[0085] This example provides a method for preparing a CoMo catalyst h-Co-MoOx / CN, and the specific steps are as follows:
[0086] Cobalt nitrate hexahydrate (0.722 g, 2.48 mmol) and 2-methylimidazole (1.629 g, 19.84 mmol) were separately dissolved in 25 ml of methanol. After ultrasonic treatment, the cobalt nitrate solution was quickly poured into an aqueous solution (10 ml) containing 45 mg of phosphomolybdic acid hydrate under stirring, and stirred for 30 min. After 30 min, the 2-methylimidazole solution was added, and stirring was continued for 3 h. After centrifugal washing, the obtained blue-violet precipitate was dried overnight in an oven at 60 °C to obtain a precursor of the CoMo catalyst h-Co-MoOx / CN. The precursor was placed in a tubular furnace and heated to 900 °C at a heating rate of 5 °C / min under an argon atmosphere and held at a constant temperature for 2 h. When cooled to 200 °C, the argon was replaced with air and held at a constant temperature for another 1.5 h to obtain the CoMo catalyst h-Co-MoOx / CN.
[0087] Figure 8c Figure 6 is the SEM image of h-Co-MoOx / CN obtained in this example. It can be seen that h-Co-MoOx / CN is completely calcined and shows an irregular morphology with a rough surface after calcination.
[0088] Example 10
[0089] This example provides a preparation method of a CoMo catalyst i-Co-MoOx / CN, and the specific steps are as follows:
[0090] Cobalt nitrate hexahydrate (0.722 g, 2.48 mmol) and 2-methylimidazole (1.629 g, 19.84 mmol) were separately dissolved in 25 ml of methanol. After ultrasonic treatment, the cobalt nitrate solution was quickly poured into an aqueous solution (10 ml) containing 45 mg of phosphomolybdic acid hydrate under stirring, and stirred for 30 min. After 30 min, the 2-methylimidazole solution was added, and stirring was continued for 3 h. After centrifugal washing, the obtained blue-violet precipitate was dried overnight in an oven at 60 °C to obtain a precursor of the CoMo catalyst i-Co-MoOx / CN. The precursor was placed in a tubular furnace and heated to 900 °C at a heating rate of 5 °C / min under an argon atmosphere and held at a constant temperature for 2 h. When cooled to 150 °C, the argon was replaced with air and held at a constant temperature for another 1.5 h to obtain the CoMo catalyst i-Co-MoOx / CN.
[0091] Figure 8d Figure 19 is the SEM image of i-Co-MoOx / CN obtained in this example. It can be seen that i-Co-MoOx / CN is completely calcined and shows an irregular morphology with a rough surface after calcination.
[0092] Example 11
[0093] Performance test of CoMo catalysts CoOx / CN, a-Co-MoOx / CN, b-Co-MoOx / CN, c-Co-MoOx / CN, d-Co-MoOx / CN, e-Co-MoOx / CN with different phosphomolybdic acid addition contents for the hydrodeoxygenation of phenol to cyclohexane.
[0094] Add 0.5 mmol of phenol, 6 ml of n-octane, and 100 mg of catalyst (CoOx / CN prepared in Example 1, a-Co-MoOx / CN prepared in Example 2, b-Co-MoOx / CN prepared in Example 3, c-Co-MoOx / CN prepared in Example 4, d-Co-MoOx / CN prepared in Example 5, e-Co-MoOx / CN prepared in Example 6) into the autoclave in sequence, fill it with 2 MPa of hydrogen, heat it to 230 °C under stirring, and keep the temperature constant for 1 h. After the reaction is completed, cool the autoclave to room temperature, separate the catalyst from the reaction solution by filtration, and analyze the reaction solution by gas chromatography-mass spectrometry.
[0095] Figure 10 It is the performance test diagram of CoMo catalysts with different phosphomolybdic acid addition contents for the hydrodeoxygenation of phenol to cyclohexane obtained in this example. Among them, c-Co-MoOx / CN shows the best catalytic performance, with a phenol conversion rate of 100% and a cyclohexane yield of 93.9%.
[0096] Example 12
[0097] Performance test of CoMo catalysts c-Co-MoOx / CN, h-Co-MoOx / CN, i-Co-MoOx / CN with different air calcination temperatures for the hydrodeoxygenation of phenol to cyclohexane.
[0098] Add 0.5 mmol of phenol, 6 ml of n-octane, and 100 mg of catalyst (c-Co-MoOx / CN prepared in Example 4, h-Co-MoOx / CN prepared in Example 9, i-Co-MoOx / CN prepared in Example 10) into the autoclave in sequence, fill it with 1 MPa of hydrogen, heat it to 230 °C under stirring, and keep the temperature constant for 3 h. After the reaction is completed, cool the autoclave to room temperature, separate the catalyst from the reaction solution by filtration, and analyze the reaction solution by gas chromatography-mass spectrometry.
[0099] Figure 11 It is the result diagram of the effect of air calcination temperature on the hydrodeoxygenation of phenol to cyclohexane obtained in this example. As the air calcination temperature decreases, the cyclohexane yield gradually decreases, and the cyclohexane yield reaches the optimum when the air calcination temperature is 250 °C.
[0100] Example 13
[0101] Performance test of CoMo catalyst c-Co-MoOx / CN for the hydrodeoxygenation of phenol to cyclohexane.
[0102] In a high-pressure reactor, 0.5 mmol of phenol, 6 ml of n-octane, and 100 mg of c-Co-MoOx / CN were added in sequence. 2 MPa of hydrogen was charged, and the mixture was heated to 230 °C under stirring and reacted at a constant temperature for 4 h. After the reaction was completed, the reactor was cooled to room temperature, and c-Co-MoOx / CN was separated from the reaction solution by filtration. The reaction solution was analyzed by gas chromatography-mass spectrometry. The conversion rate of phenol was 100%, and the yield of cyclohexane was 91.3%.
[0103] Figure 12 It is the performance test result diagram of c-Co-MoOx / CN obtained in this example. As the reaction time extended, the yield of cyclohexane showed a trend of increasing first and then decreasing. Among them, the yield of cyclohexane reached the optimum when the reaction time was 3 h.
[0104] Example 14
[0105] Effect of reaction pressure on the hydrodeoxygenation of phenol to cyclohexane.
[0106] In a high-pressure reactor, 0.5 mmol of phenol, 6 ml of n-octane, and 100 mg of c-Co-MoOx / CN were added in sequence. Hydrogen at 0.5 MPa, 1 MPa, 1.5 MPa, and 2 MPa was charged respectively, and the mixture was heated to 230 °C under stirring and reacted at a constant temperature for 3 h. After the reaction was completed, the reactor was cooled to room temperature, and c-Co-MoOx / CN was separated from the reaction solution by filtration. The reaction solution was analyzed by gas chromatography-mass spectrometry.
[0107] Figure 13 It is the result diagram of the effect of reaction pressure on the hydrodeoxygenation of phenol to cyclohexane obtained in this example. As the reaction pressure increased, the change in the yield of cyclohexane was relatively small. Among them, the yield of cyclohexane reached the optimum of 93.9% when the reaction pressure was 2 MPa, but the yield of cyclohexane also reached 88.3% when the reaction pressure was 0.5 MPa.
[0108] It should be understood that the detailed description of the technical solution of the present invention with the aid of the optimized examples is illustrative rather than restrictive. It cannot be determined that the specific implementation manners of the present invention are limited to this. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, modifying the technical solutions recorded in each example, or equivalently replacing some of the technical features, should all be regarded as belonging to the patent protection scope determined by the claims submitted by the present invention.
[0109] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, rather than limitations on the implementation manners of the present invention. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to enumerate all implementation manners here. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a CoMo catalyst suitable for phenol hydrodeoxygenation reaction, characterized in that: The steps include: (1) dissolving a molybdenum heteropoly acid and a cobalt salt in deionized water and methanol, respectively, to obtain a metal cobalt salt solution and a metal molybdenum heteropoly acid solution; dissolving an organic ligand in methanol to obtain an organic ligand solution; (2) pouring the metal cobalt salt solution into the metal molybdenum heteropoly acid solution at room temperature, mixing and stirring, then adding the organic ligand solution, continuing to stir, centrifugation washing and drying, to obtain the precursor CoMo bimetallic MOFs; (3) The precursor CoMo bimetallic MOFs prepared in step (2) is subjected to two-step pyrolysis in a tube furnace, The CoMo catalyst Co-MoOx / CN is obtained.
2. The method for preparing the CoMo catalyst Co-MoOx / CN according to claim 1, characterized in that: In step (1), the molybdic acid is phosphomolybdic acid hydrate; the cobalt salt is cobalt nitrate hexahydrate; and the organic ligand is 2-methylimidazole.
3. The method for preparing the CoMo catalyst Co-MoOx / CN according to claim 1, characterized in that: In step (1), the concentration of the metal cobalt salt solution is 0.05-0.1 mol / L, the concentration of the metal molybdenum heteropoly acid solution is 0-0.005 mol / L, and the concentration of the organic ligand solution is 0.5-1 mol / L.
4. The method for preparing the CoMo catalyst Co-MoOx / CN according to claim 1, characterized in that: In step (1), the volume ratio of the added amounts of the metal cobalt salt solution, the metal molybdenum heteropoly acid solution and the organic ligand solution is 1:1:1 to 5:1:
5.
5. The method for preparing the CoMo catalyst Co-MoOx / CN according to claim 1, characterized in that: In step (2), the mixing and stirring time is 0.2 to 0.8 h; and the stirring time after adding the 2-methylimidazole solution is 1 to 5 h.
6. The method for preparing the CoMo catalyst Co-MoOx / CN according to claim 1, characterized in that: In step (3), the two steps of pyrolysis are carried out under argon and air respectively.
7. The method for preparing the CoMo catalyst Co-MoOx / CN according to claim 1, characterized in that: In step (3), the pyrolysis temperature under argon atmosphere is 700-900° C., and the pyrolysis time is 1-4 hours.
8. The method for preparing the CoMo catalyst Co-MoOx / CN according to claim 1, characterized in that: In step (3), the pyrolysis temperature in air atmosphere is 150-250° C., and the pyrolysis time is 1-3 hours.
9. A CoMo catalyst Co-MoOx / CN suitable for phenol hydrodeoxygenation reaction prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The carbon in the material is in an amorphous state, and the metal particles are evenly distributed on the carbon carrier.
10. The CoMo catalyst according to claim 9 is used in the hydrodeoxygenation reaction of phenol, characterized in that: Phenol, n-octane and CoMo catalyst Co-MoOx / CN are sequentially added into a high-pressure reactor, hydrogen is introduced, and the reactor is heated to 200-240° C. under stirring, and the reaction is carried out at a constant temperature for 0.5-4 hours. After the reaction is completed, the reactor is cooled to room temperature, and the CoMo catalyst Co-MoOx / CN is separated from the reaction solution by filtration to obtain cyclohexane. The mass ratio of phenol to the CoMo catalyst Co-MoOx / CN is 0.1-0.9.